Tanda-tanda Ketoksikan pada Tikus Wistar dengan Administrasi Oral Subakut Ekstrak Kloroform Daun Lidah Mertua (Sansevieria trifasciata) - Fitria, Laksmindra; Gunawan, Isma Cahya Putri; Sanjaya, Wilda Bunga Tina (Biota, 2024)
Snake Plant (Sansevieria trifasciata) has been commonly used as traditional herbal medicine in addition to being ornamental plant and phytoremediation agent. Toxicity studies on pharmaceutical substances are required to assess the level of hazard and safety before processing as drugs. Conventional toxicity test focused on determining LD50, despite the fact that not all substances induce death in experimental animals. They might survive but suffering or get sick. This study aimed to evaluate safety level of oral administration of chloroform extract of S. trifasciata leaves (CESTL) for 28 days (subacute) in Wistar rats (Rattus norvegicus) as model animal through the observation of clinical signs that lead to lethal and sublethal effects. The procedure referred to OECD Guideline No. 407 with the dose of CESTL was 1000 mg/kg bw (Limit Test). Adult female nulliparous Wistar rats were assigned into three groups which received CESTL, Tween 4 % (solvent for CESTL), or distilled water as control (placebo) 1 mL/individual/day. Parameters observed consisted of mortality, general physical examination, individual and social activity and behavior, body weight, body temperature, food intake, water consumption, fecal condition, and fasting blood glucose (FBG) level. Results showed that no animals died or suffered as a result of CESTL poisoning. There were no significant differences in all parameters value among three groups, indicating that CESTL did not generate adverse effects on animal normal physiological condition. Thus, it can be concluded that CESTL at the dose of 1000 mg/kg bw is relatively safe for consumption during subacute period.